Local wisdom Pasang ri Kajang as a political power in maintaining indigenous people's rights - Kambo, Gustiana Anwar (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This research analyzes Pasang ri Kajang as local wisdom in Indigenous people Ammatoa Kajang becomes a social and political power. It maintains the existence of indigenous people Ammatoa Kajang in the customary land conflict with PT London Sumatra (Lonsum). Indigenous Peoples of Ammatoa Kajang, known as indigenous people who uphold the values ​​of local wisdom, was called Pasang ri Kajang; one of them is their belief that forests are the center of life. The conflict has arisen since PT Lonsum has unilaterally taken over Ammatoa Kajang's customary land in several villages. The lack of regulation of the local government that protects the rights of the Kajang community makes the position of the Ammatoa Kajang indigenous community weak in resisting. The indigenous Ammatoa Kajang community and several environmental and indigenous peoples' institutions demanded that the Bulukumba district government make and ratify the Ranperda of the Ammatoa Kajang community that could protect the rights and recognition of the Ammatoa Kajang customary community. At the end of 2015, the Bulukumba district government ratified regional regulation No. 9/2015 about the Inauguration, Recognition, and Protection of Customary Law Communities Ammatoa Kajang. Ratification of this regulation is a form of deregulation carried out by the Bulukumba district government in responding to conflicts over land and forest struggles of the indigenous people of Ammatoa Kajang and PT. Lonsum.